Paperworks: 'Language' writing and media change. Issue 2 (1st February 2021) - Byers, Mark
ABSTRACT: 'Language' writing is frequently understood as a response to the collapse of the New Left and the entrenchment of post-Fordist economics in the 1970s. In this essay, I propose a third key context for this loosely-defined movement: the arrival of electronic and digital word-processing systems in the American workplace and, increasingly, the middle-class American home. Foregrounding contemporary accounts of these systems, I suggest that the textual politics of 'Language' writing, as well as its bibliographical experiments (or 'paperworks'), constituted a variety of media critique; questioning and contesting a shift towards textual automation and fluidity which had become crucial to the American service and information sectors. Drawing special attention to the issue of screen textuality, the essay examines key works by Ron Silliman and Lyn Hejinian in the period 1976–83 in the light of these media transitions, arguing for a media historical account of the movement, perhaps the last analogue avant-garde.